Automated backlash determination on rack-and-pinion drives - Zenn, Wiebke; Keck, Alexander; Beck, Marcus; Herold, Sven; Melz, Tobias (IEEE/ASME International Conference on Advanced Intelligent Mechatronics, 2023)
One characteristic of rack-and-pinion drives is that they are usually subject to backlash. In non-high precision applications, such as laser cutting, a certain amount of backlash is tolerated. However, changes in the amount of backlash are often related to a fault or damage in the machine. For this reason, it can be useful to monitor the size of the backlash. In this paper, a new method for the determination of backlash in rack-and-pinion drives is introduced and applied to single axes as well as to machines with gantry axes. Since in non-high precision applications there is generally no direct measuring system to detect the output-side position, an additional MEMS acceleration sensor is attached to the moving load. Its sensor signal is compared with the motor acceleration obtained from the differentiation of the measured motor speed during a positioning step. With these two acceleration signals, the beginning and the end of the change of the tooth flanks can be identified automatically considering the machine dynamics. From this, the size of the backlash can be determined. It is shown that an automated determination of the backlash is possible even for applications with highly complex machine dynamics.